2019
DOI: 10.1371/journal.pone.0214648
|View full text |Cite
|
Sign up to set email alerts
|

First clinical isolate of Escherichia coli harboring mcr-1 gene in Mexico

Abstract: Our aim in this report was to describe the characteristics of the first clinical isolate of Escherichia coli (EC-PAG-733) harboring the mcr- 1 gene found in Mexico. This isolate was obtained from a fecal sample from a young child with an oncological condition. We obtained the whole-genome sequence using next-generation sequencing and analyzed the sequence by bioinformatics tools. EC-PAG-733 was resistant to third- and fourth-generation cephalosporins and was suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Strain NMBU_W13E19 displayed the gene combination eilA, Air and lpfA (encoding for long polar fimbriae) that was recently reported from a bla CTX−M -producing E. coli strain isolated from a wastewater treatment plant in China (Jiang et al, 2019) and in eight food-producing animal isolates (seven turkey and one laying hen) in Poland (Zajac et al, 2019). This particular gene combination was also seen in the first clinical isolate of an E. coli harboring the mcr-1 gene in Mexico, isolated in 2017 (Merida-Vieyra et al, 2019), as well as in six ESBL-producing E. coli strains isolated from veterinary hospital staff and students in three United Kingdom veterinary hospitals (Royden et al, 2019). The NMBU_W12E19 strain has an unusual array of virulence genes when compared to typical and atypical EAEC strains.…”
Section: Detection Of Virulence Factorsmentioning
confidence: 60%
“…Strain NMBU_W13E19 displayed the gene combination eilA, Air and lpfA (encoding for long polar fimbriae) that was recently reported from a bla CTX−M -producing E. coli strain isolated from a wastewater treatment plant in China (Jiang et al, 2019) and in eight food-producing animal isolates (seven turkey and one laying hen) in Poland (Zajac et al, 2019). This particular gene combination was also seen in the first clinical isolate of an E. coli harboring the mcr-1 gene in Mexico, isolated in 2017 (Merida-Vieyra et al, 2019), as well as in six ESBL-producing E. coli strains isolated from veterinary hospital staff and students in three United Kingdom veterinary hospitals (Royden et al, 2019). The NMBU_W12E19 strain has an unusual array of virulence genes when compared to typical and atypical EAEC strains.…”
Section: Detection Of Virulence Factorsmentioning
confidence: 60%
“…Whereas in high-income nations the prevalence of E. coli strains resistant to antibiotics colonizing the gastrointestinal system of neonates is low [38], in lowincome countries the prevalence of E. coli strains resistant to antibiotics such as tetracycline, ampicillin and trimethoprim/sulfamethoxazole exceeds 50% [39]. Fecal colonization of humans by resistant E. coli is on the rise around the world since the mid-2000s and the situation has worsened as fecal colonization by strains resistant to last-resource antibiotics, such as colistin, has been recently reported in different countries [40,41]. As the prevalence of fecal colonization by these E. coli strains increase, so will the number of human infections caused by them, as it has been previously shown that fecal colonization with resistant microorganisms increases the risk factor of developing urinary tract infections by a factor of 13.0 [31].…”
Section: Hygiene/fecal Colonizationmentioning
confidence: 99%
“…Although additional mcr genes, including mcr-2 , mcr-3 , and mcr-4 , have been identified, mcr-1 remains the predominant colistin resistance gene in China ( Yassin et al., 2017 ). The distribution of mcr-1– containing strains is global, with MDR strains being isolated in Asia, Europe, the United States, and Australia ( Ellem et al., 2017 , Hernandez et al., 2017 , Lindsey et al., 2017 , Meinersmann et al., 2017 , Wang et al., 2017a , Wang et al., 2017b ; Yang et al., 2017 , Garza-Ramos et al., 2018 , Rau et al., 2018 , Creighton et al., 2019 , Henig et al., 2019 , Macesic et al., 2019 , Merida-Vieyra et al., 2019 , Moreno et al., 2019 ). This demonstrates that mcr-1 genes carried by plasmids have strong transmission capacity.…”
Section: Introductionmentioning
confidence: 99%